Mathematical Modeling of Salmonella Cancer Therapies Demonstrates the Necessity of Both Bacterial Cytotoxicity and Immune Activation - Lars M. Howell; Neil S. Forbes (Bioengineering)
Salmonella therapies are a promising tool for the treatment of solid tumors. Salmonella can be engineered to increase their tumor infiltration, cell killing abilities, and immunostimulatory properties. However, bacterial therapies have often failed in clinical trials due to poor characterization. Mathematical models are useful for predicting the immune response to cancer treatments and characterizing the properties of bacterial invasion. Herein we develop an ordinary differential equation-based model that combines bacterial therapies with classical anti-tumor immunotherapies. Our modeling results suggest that increasing bacterial localization to the tumor is key for therapeutic efficacy; however, increased intracellular invasion and direct bacterial mediated cytotoxicity does not reduce tumor growth. Further, the model suggests that enhancing T cell-mediated cell death by both bacterial stimulation of pro-inflammatory cytokines and activation of T cells via antigen cascade is critical for therapeutic efficacy. A balance of intracellular and extracellular Salmonella leads to more effective therapeutic response, which suggests a strategy for strain design to be tested in vivo. Overall, this model provides a system to predict which engineered features of Salmonella therapies lead to effective treatment outcomes.